Mussel farms drive species replacement through ecological drift and dispersal - Cynthia Vásquez; Renato A. Quiñones; Oscar Díaz; Nicolas Rozbaczylo; Jorge Pérez-Schultheiss; Eduardo Hernández-Miranda (Environmental and Sustainability Indicators)
Mussel farms can introduce disturbances to the diversity of soft bottom benthic macroinvertebrate communities. This study aimed to evaluate the ecological processes and mechanisms underlying responses from communities in two mussel farming areas in Chile, which is the largest exporter in the world. Alpha diversity indices, additive beta partitioning, and the Raup-Crick null model were employed for analysis. Results indicate a significant impact of mussel farming on both alpha and beta diversity, primarily through species replacement processes, and neutral mechanisms of ecological drift and dispersal. Alpha diversity decreased, and beta diversity increased near the farm areas with reduced hypoxic sediments. These results have conservation implications, especially considering that mussel farming in Chile is concentrated in regions with high levels of endemism. Because ecological drift is more pronounced in small communities with low dispersal potential, endemic and rare species are more susceptible to local extinction. A metacommunity and neutral approach should be integrated into future studies and environmental regulations to improve the assessment of the impacts of mussel farming on diversity.